Ectomycorrhizal fungi of Salix rotundifolia III. Resynthesized mycorrhizal complexes and their surface phosphatase activities - Antibus, R. K.; Croxdale, J. G.; Miller, O. K.; Linkins, A. E. (Canadian Journal of Botany, 1981)
Pure culture isolates were obtained from fungi fruiting in the vicinity of dwarf willows at Barrow and Cape Simpson, Alaska. Four of these isolates and one isolate from Maryland were tested for their ability to form ectomycorrhizae with cuttings of Salix rotundifolia under controlled environmental conditions. Isolates of Entoloma sericeum, Hebelomapusillum, and Cenococcum geophilum from Barrow and Cape Simpson, Alaska all formed typical ectomycorrhizae with S. rotundifolia, while an isolate of C. geophilum from a temperate ecosystem (Maryland) did not.All of the ectomycorrhizae synthesized with S. rotundifolia, plus uncolonized roots, demonstrated an ability to hydrolyze p-nitrophenyl phosphate at a pH of 4.7. The acid phosphatase activity of E. sericeum ectomycorrhizae was from 10 to 40 times as great as that demonstrated by other mycorrhizal and nonmycorrhizal roots on a surface area basis.